Testing environmental controls on methane generation during microbial degradation of coal and oil from the Cherokee basin, Kansas - Tummons, Michael A. (Kansas State University, 2017)
Biodegradation of crude oil to methane has long been known to exist in shallow petroleum reservoirs. It is only in the past decade, however, in which the concept of in-reservoir petroleum biodegradation has changed from a model emphasizing aerobic crude-oil degradation (with oxygen delivered down from meteoric waters) to a more recent model in which crude-oil degradation is driven by anaerobic processes (methanogenic microorganisms). In this study, we examine controls on microbial conversion of crude oil and coal into methane in middle-Pennsylvanian strata in the Cherokee Basin, Kansas, USA and how access to oil or coal influence microbial communities. Specifically, we considered the following hypotheses: 1) microorganisms in the basin are capable of generating methane by degrading crude oil or coal and 2) potential controls on the rate of methane formation include microbial diversity, formation water chemistry, nutrient abundance, and carbon dioxide abundance. To test these hypotheses, we used three sets of laboratory experiments constructed of materials from the Cherokee basin, Kansas. One set tested environmental controls on methane generation from oil, another from coal, and a third was a control experiment that utilized methanogenic substrates rather than oil or coal. In the experiments with oil and coal, environmental factors tested ammonium/phosphate availability, feedlot wastewater injection, and carbon dioxide abundance. Our experiments also tested the influence of salinity, by including materials from a well producing water with relatively low salinity and a well producing water with relatively high salinity. The cultures were allowed to incubate from approximately 75 to 170 days, during which headspace of oil and coal bioreactors were sampled periodically and analyzed for methane concentrations. Post incubation analyses included microbial DNA sequencing. We determined that a higher concertation of methanogens existed in the lower salinity well, which has higher potential for practical stimulatory injection. Of methane produced, the only significant (Mann Whitney) treatment had access to oil in lower salinity formation water. Access to coal resulted in no significant results. Microbial diversity, in the form of methanogenic archaea abundance, formation water chemistry (salinity), and wastewater nutrient often correlated with increased, yet insignificant, rates of methane production, while carbon dioxide abundance showed no benefit. Of methanogenic substrates consumed, we determined that most Cherokee basin methanogens preferred methanol over hydrogen and acetate.
Keywords: Natural Gas; Stimulation; Methane; Archaea; Coalbed; Microbiology